1999
DOI: 10.2105/ajph.89.8.1244
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent reproductive events and subsequent breast cancer risk.

Abstract: BriefsConnecticut and its influence on the reporting of melanoma. JAm Acad Dermatol. 1992;26: 198-202. 11. Karagas MR, Thomas DB, Roth GJ, Johnson LK, Weiss NS. The effects of changes in health care delivery on the reported incidence of cutaneous melanoma in western Washington State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…Our overall null association for breast cancer as it relates to induced abortion is in agreement with several recent casecontrol studies conducted among women of all age groups, 9 -11 and restricted to younger women. [12][13][14] We are also in agreement with 2 recent cohort studies that reported relative risks of 1.0 (95% CI 0.94 -1.06) 15 and 1.1 (95% CI 0.8 -1.6), 2 respectively. Nor did we find an increased risk associated with several induced abortions.…”
Section: Resultssupporting
confidence: 92%
“…Our overall null association for breast cancer as it relates to induced abortion is in agreement with several recent casecontrol studies conducted among women of all age groups, 9 -11 and restricted to younger women. [12][13][14] We are also in agreement with 2 recent cohort studies that reported relative risks of 1.0 (95% CI 0.94 -1.06) 15 and 1.1 (95% CI 0.8 -1.6), 2 respectively. Nor did we find an increased risk associated with several induced abortions.…”
Section: Resultssupporting
confidence: 92%
“…However, the absence of the common 19-repeat allele in the IGF1 gene is associated with high IGF-1 levels during OC use in nulliparous women (Jernström et al, 2001a, b). The risk of early-onset breast cancer after teenage OC use varies considerably between ethnic groups (Marcus et al, 1999), and appears to correlate with the relative frequencies of the absence of the 19-repeat allele among these ethnic groups (Jernström et al, 2001a). In addition, the absence of the 19-repeat allele appears to mitigate the normal agerelated decline in IGF-1 levels (Rietveld et al, 2003).…”
mentioning
confidence: 99%
“…Outro fator pouco estudado e que tem grande impacto no futuro da adolescente é a relação entre amamentação e o risco de câncer de mama. Ao engravidar, as mamas passam por um processo de maturação, o que se considera fator de proteção contra o câncer de mama 34,35 . Há evidências também da proteção da amamentação contra alguns tipos de câncer epitelial do ovário 35 .…”
Section: Implicações Para O Desenvolvimento Da Adolescenteunclassified